The impact of comorbidities on tuberculosis treatment outcomes in Poland: a national cohort study - Nowiński, Adam; Wesołowski, Stefan; Korzeniewska-Koseła, Maria (Frontiers in Public Health, 2023)
Background: Tuberculosis (TB) is a complex disease associated with other medical conditions, that may affect disease severity. This study aimed to investigate the impact of comorbidities on treatment outcomes and mortality rates in patients with TB in Poland.Methods: We analyzed a national cohort of 19,217 adult TB patients diagnosed between 2011 and 2016 in Poland. We compared treatment success rates and mortality rates in patients with comorbidities and those without to assess the impact of various comorbidities on these outcomes. Odds ratios (OR) were calculated to quantify the association between comorbidities and TB treatment outcomes.Results: Patients with comorbidities had lower treatment success rates and higher mortality rates. Diabetes was identified as a significant risk factor for increased TB mortality (OR = 1.9) and mortality from all other causes (OR = 4.5). Similar associations were found for alcoholism (OR = 8.3 and OR = 7.1), immunosuppressive therapy (OR = 5.7 and OR = 5.9), and cancer (OR = 3.4 and OR = 15.4). HIV and tobacco use were associated with an increased risk of mortality from causes other than TB, with odds ratios of 28.6 and 2.2, respectively. The overall treatment success rate in the study population was 88.0%, with 9.2% of patients failing to achieve treatment success and 2.8% dying. Comorbidities such as diabetes, alcoholism, substance addiction, immunosuppressive therapy, cancer, and tobacco use increased the risk of tuberculosis treatment failure.Conclusions: Patients with comorbidities face a higher risk of unsuccessful treatment outcomes and increased mortality. It is essential to implement integrated management strategies that address both TB and comorbid conditions to improve treatment success rates and reduce mortality.